Will the amendments to the IAS 16 and IAS 41 influence the value of biological assets? - Bohušová, Hana; Svoboda, Patrik (Česká akademie zemědělských věd, 2017)
The aim of the paper is the evaluation of the impact of the new amendments to the IAS 16 and IAS 41 - Agriculture: Bearer Plants on the financial reporting in agriculture. The paper is based on the comparison of the current treatments for biological assets in a form of bearer plants measurement using the IFRS13 methodology and the treatments of the amendments to the IAS 16 and IAS 41. Statistical data regarding the selected bearer plant were used for the quantification. The orchard of fruit trees was considered as a suitable representative of bearer plants. As it is clear from the results of the research, the measurement at fair value using the DCF method is based on the estimation which requires a relatively large source of input data for this estimation over the useful life of bearer plants. On the other hand, the effect on the value of the assets could be controversial and the effect on the profit or loss during the useful life could be volatile. Although the objective of the fair value measurement is to achieve a true and fair view, in this case, the fulfilment of this objective is at least controversial, since the biological assets in the form of bearer plants cannot be separately traded.
Keywords: Agriculture; Bearer assets; IAS 41; Measurement of agricultural assets; Plants